KORELASI DAN SIDIK LINTAS KARAKTER PERTUMBUHAN DAN KOMPONEN HASIL DENGAN HASIL PADA 15 GENOTIPE HIBRIDA JAGUNG - Hellianti Pennita; Catur Herison; Marwanto Marwanto; Rustikawati Rustikawati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[PATH ANALYSIS OF GROWTH CHARACTERS AND YIELD COMPONENTS WITH THE YIELD OF 15 GENOTYPES OF MAIZE HYBRID].  Determination of traits used as the selection criteria are based on the trait(s) that have a close relationship to the yield.  The aims of this research were to measure the closeness of the relationship between morphological (growth and yield component) traits and crop yield, and to determine the trait that directly or indirectly affected on maize yield.  The research was conducted in Rimbo Kedui’s Village, South Seluma Subdistrict, Seluma District, Bengkulu Province on May 2017 to August 2017.  The experimental design used was a Complete Randomized Block Design (CRBD) in a single factor with 3 replications.  The treatments were 15 maize hybrid genotypes, consisting of CT1, CT2, CT3, CT4, CT5, CT6, CT7, CT8, CT9, CT10, CT11, CT12, CT13, CT14, and CT15.  The data were statistically analyzed by analysis of varians (ANOVA) with P(a=5%).  The qualitative data were analyzed descriptively. The result of correlation analysis revealed that the yield of maize hybrids highly correlated to some growth and yield component factors.  High-yielding maize hybrids were supported by higher ear diameter, plant fresh weight, plant dry weight, plant height, the number of seeds per ear.  Plant dry weight became the variable that has the highest direct effect with positive correlation on the yield.  The second highest rank was the number of seeds per ear with also a positive correlation value.  Yield improvement of maize hybrid, therefore, can be obtained by fostering the plant total biomass and/or by multiplying the number of seeds per ear.